Review of Maurizio Isabella and Konstantina Zanou, eds, Mediterranean Diasporas: Politics and Ideas in the Long 19th Century - Greene, Molly (Historein, 2017)
Maurizio Isabella and Konstantina Zanou, eds. Mediterranean Diasporas: Politics and Ideas in the Long 19th Century. London: Bloomsbury Academic, 2016. xiii + 217 pages